Expansion of the fatty acyl reductase gene family shaped pheromone communication in Hymenoptera - Tupec, Michal; Buček, Aleš; Janoušek, Václav; Vogel, Heiko; Prchalová, Darina; Kindl, Jiří; Pavlíčková, Tereza; Wenzelová, Petra; Jahn, Ullrich; Valterová, Irena; Pichová, Iva (eLife, 2019)
Fatty acyl reductases (FARs) are involved in the biosynthesis of fatty alcohols that serve a range of biological roles. Insects typically harbor numerous FAR gene family members. While some FARs are involved in pheromone biosynthesis, the biological significance of the large number of FARs in insect genomes remains unclear. Using bumble bee (Bombini) FAR expression analysis and functional characterization, hymenopteran FAR gene tree reconstruction, and inspection of transposable elements (TEs) in the genomic environment of FARs, we uncovered a massive expansion of the FAR gene family in Hymenoptera, presumably facilitated by TEs. The expansion occurred in the common ancestor of bumble bees and stingless bees (Meliponini). We found that bumble bee FARs from the expanded FAR-A ortholog group contribute to the species-specific pheromone composition. Our results indicate that expansion and functional diversification of the FAR gene family played a key role in the evolution of pheromone communication in Hymenoptera.
Keywords: Animals; mastné alkoholy; Bombus terrestris; evolutionary biology; sekvence aminokyselin; Bombus lapidarius; transposable elements; transpozibilní elementy DNA; Amino Acid Sequence; aldehydoxidoreduktasy; Phylogeny; DNA Transposable Elements; gene family evolution; Aldehyde Oxidoreductases; Pheromones; Fatty Alcohols; fatty acyl reductases; zvířata; feromony; fylogeneze; Hymenoptera; Bombus lucorum